Análisis Histórico de la educación especial en la provincia de Imbabura - Ponce Mejía, Franklin Heriberto (2015)
This research leads to analyse the history of Special Education in the world. In our country, Ecuador, which appeared since 1940, but at the initiative of Parents, the Special Education “Ibarra” Institute was created in the Imbabura Province emerged in 1979, and then years later, it was strengthened with the Special Education Department. The impact of the models, which benefited the Education of People with Disabilities, according to several authors’ view, the same helped us to understand how the education has had problems and successes from its beginnings until today. To understand and analyze the evolution of Special Education in the Imbabura Province from its beginnings to the present, it carried out a field research was conducted from the perspective of Special Education Professionals, Regular Education Professionals, Parents, Persons with disabilities over 30 years; the Former Head of the Special Education Department, the Coordinator of Conadis-Imbabura, Director of the Cultural Department of the Autonomous Desentralized Government -Ibarra, by applying surveys and interviews respectively, with non random sample which allowed us to know the situation of Special Education in the Province. The Models of Attention applied to education and provided to students with disabilities inside the ecuadorian education system are: Inclusive Education Model for Regular Education and Functional Ecological Model for Specialized Education. Therefore, the disability is not a hindrance whereby a person is proposed. Education will enable to break through in all areas and people will reach both personal and professional success.